2003
DOI: 10.1126/science.1079293
|View full text |Cite
|
Sign up to set email alerts
|

Endoproteolytic Activity of the Proteasome

Abstract: The proteasome plays a central role in the degradation of regulatory and misfolded proteins. Current models suggest that substrates access the internal catalytic sites by processively threading their termini through the gated substrate channel. Here, we found that latent (closed) and activated (open) proteasomes degraded two natively disordered substrates at internal peptide bonds even when they lacked accessible termini, suggesting that these substrates themselves promoted gating of the proteasome. This endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
345
2
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(365 citation statements)
references
References 30 publications
13
345
2
5
Order By: Relevance
“…In many cases, if a protein can be delivered to the proteasome in a denatured or partially unfolded state, ubiquitination should not be required for its degradation. In fact, p21 and a-synuclein that are considered 'naturally unstructured' proteins can be degraded in vitro by the proteasome, in the absence of ubiquitination (Liu et al, 2003). It has been reported that ARF can be subjected to N-terminal ubiquitination, a process independent from p53 and Mdm2 (Kuo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, if a protein can be delivered to the proteasome in a denatured or partially unfolded state, ubiquitination should not be required for its degradation. In fact, p21 and a-synuclein that are considered 'naturally unstructured' proteins can be degraded in vitro by the proteasome, in the absence of ubiquitination (Liu et al, 2003). It has been reported that ARF can be subjected to N-terminal ubiquitination, a process independent from p53 and Mdm2 (Kuo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro translated p14ARF was incubated with 20S proteasome at 371C for the indicated time intervals (Figure 6d). As controls, we used in vitro translated p21, that has been shown to be naturally unstructured and degraded in vitro by the 20S proteasome (Liu et al, 2003) and TBP-1. As shown, ARF is degraded by the 20S proteasome as efficiently as p21 and accumulates after treatment with proteasome inhibitor, whereas TBP-1 levels are unchanged.…”
Section: Tbp-1 Regulates P14arf Oncosuppressor a Pollice Et Almentioning
confidence: 99%
“…Investigations of substrate binding, release and degradation of side-on and bottom immobilized proteasomes revealed that one entry to the proteolytic chamber is sufficient for substrate access and release of the products (125). A positive cooperativity of substrate binding has been shown: The proteasome can degrade two substrates at the same time, as well as it can cleave proteins without accessible ''ends'' while showing endoproteolytic behavior (126). It is supposed that cleavage products leave the proteasome mainly via the (opposite) substrate entry but it could be possible to release short peptides through gaps between the a-and b-rings that are still too small to allow substrate access (127).…”
Section: The Degradation Of Oxidized Proteins-a Function Of the 20s Pmentioning
confidence: 99%
“…Proteasomal activity is essential in maintaining low-level basal p21 Cip1/Waf1 protein expression by regulating its degradation. [12][13][14][15] The murine double minute 2 (MDM2) oncogene is amplified and overexpressed in numerous human cancers [16][17][18][19] including Rhabdomyosarcoma (RMS) tumors and cell lines. 20,21 MDM2 negatively regulates p53 transcriptional activity 18,22 and promotes p53 degradation by the proteasome.…”
mentioning
confidence: 99%